2021
DOI: 10.1108/md-05-2020-0545
|View full text |Cite
|
Sign up to set email alerts
|

A measure of innovation performance: the Innovation Patent Index

Abstract: PurposeThe measure of companies' Innovation Performance is fundamental for enhancing the value and decision-making processes of firms. The purpose of this paper is to present a new measure of Innovation Performance, called Innovation Patent Index (IPI), which makes it possible to quantitatively summarize different aspects of firms' innovation.Design/methodology/approachIn order to define the IPI, a secondary source, i.e. patent data, has been used. The five dimensions of IPI, i.e. efficiency, time, diversifica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(37 citation statements)
references
References 72 publications
(124 reference statements)
2
32
0
3
Order By: Relevance
“…They only blindly depend on Technology readiness levels (TRL) to measure innovation level overall. By the present results, previous studies have demonstrated that innovation performance evaluation is essential for raising a company's worth and strengthening the decision-making process (Ponta, 2021). This shows the reason why processes scored the lowest.…”
Section: Theme 6: Research and Developmentsupporting
confidence: 71%
“…They only blindly depend on Technology readiness levels (TRL) to measure innovation level overall. By the present results, previous studies have demonstrated that innovation performance evaluation is essential for raising a company's worth and strengthening the decision-making process (Ponta, 2021). This shows the reason why processes scored the lowest.…”
Section: Theme 6: Research and Developmentsupporting
confidence: 71%
“…Patents are closer to application and can provide more innovation information (Archibugi, 1988). In empirical analyses, patents are usually used as an indicator of innovation (e.g., Abraham & Moitra, 2001; Kremer, 1998; Ponta et al., 2021; Wang et al., 2021). Scholars also try to improve patents quality (Lanjouw & Schankerman, 2004).…”
Section: Methodsmentioning
confidence: 99%
“…Era distrupsi saat ini memaksa para pelaku UMKM untuk memiliki bisnis mindset dan jiwa kompetitif yang kuat, mau merespon kondisi persaingan bisnis dengan melakukan inovasi serta (Ponta et al, 2021). Kemampuan untuk beradaptasi dan bertransformasi menjadi penting karena kalau tidak bisa melakukannya, maka dampaknya perusahaan akan tiidak mendapatkan tempat di hati pelanggan, akhirnya produknya tidak diserap oleh market dan jangka panjang perusahaan harus mmenutup usahanya karena kurangnya kepiwaian dalam menjalankan bisnis sesuai dengan era dan perkembangan yang terjadi.…”
Section: Pendahuluanunclassified